2000
DOI: 10.1562/0031-8655(2000)072<0709:aosopo>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Structure of Photoreceptor Organelle and Blepharismin-associated Protein in Unicellular Eukaryote Blepharisma¶

Abstract: In the ciliated protozoan Blepharisma, step-up photophobic response is believed to be mediated by a novel type of photosensory pigment known as "blepharismins" (BL) that are contained in the pigment granules located just beneath the plasma membrane. We examined the ultrastructure of the pigment granules by freeze-fracture and thin-section electron microscopy and proposed a schematic diagram showing the granules' three-dimensional inner membranous structure. Some of the BL are suggested to be associated with 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Blue cells were washed, collected by low speed centrifugation, and resuspended in a 20 mmol L −1 sodium cholate (NaCh) solution. The OBIP chromoprotein was purified by liquid chromatography of this preparation on a hydroxyapatite column. ,, The protocol closely follows the one described by Checcucci et al, which proved to yield samples mainly containing the 200 kDa (SDS-PAGE determination) OBIP protein. The purity of our sample was not quantified.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Blue cells were washed, collected by low speed centrifugation, and resuspended in a 20 mmol L −1 sodium cholate (NaCh) solution. The OBIP chromoprotein was purified by liquid chromatography of this preparation on a hydroxyapatite column. ,, The protocol closely follows the one described by Checcucci et al, which proved to yield samples mainly containing the 200 kDa (SDS-PAGE determination) OBIP protein. The purity of our sample was not quantified.…”
Section: Methodsmentioning
confidence: 99%
“…Studying the primary photoprocesses involved in biological photoreceptors is a fascinating field that teaches us on the various solutions evolved by Nature in order to convert light into a biological signal. Most of the known light-sensing proteins belong to one of the following six families: rhodopsins, phytochromes, xanthopsins, cryptochromes, phototropins, and BLUF proteins. , The chromoprotein thought to be responsible for the step-up photophobic response of Blepharisma japonicum nevertheless belongs to a different family. B. japonicum is a red-colored photophobic ciliated protozoan, the biology of which was described by Giese…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fabczak et al (2001) reported that phosphorylation of two other proteins, 28and 46-kDa proteins, of B. japonicum is down-and up-regulated by light, respectively. They suggest that the phosphorylated; 46-kDa protein may associate with or be a proteolytic digest product from the 200-kDa protein (Matsuoka et al, 2000). The large discrepancy between these two values of mol wt has not been resolved.…”
Section: Ciliate Photoreceptorsmentioning
confidence: 99%